2008
DOI: 10.1111/j.1753-4887.2008.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D's role in cell proliferation and differentiation

Abstract: Vitamin D has pleiotropic effects that go beyond its traditional role in calcium homeostasis. Hundreds of genes with vitamin D receptor response elements directly or indirectly influence cell cycling and proliferation, differentiation, and apoptosis. Vitamin D compounds also have effects on cell function that are nongenomic. The noncalcemic actions of vitamin D influence normal and pathological cell growth, carcinogenesis, immune function, and cardiovascular physiology. This review examines many of the various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
190
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(209 citation statements)
references
References 80 publications
(181 reference statements)
10
190
1
8
Order By: Relevance
“…The most commonly reported effect has been observed due to an arrest at G0/G1 to S transition of cell cycle through multiple mechanisms (Samuel & Sitrin, 2008). Several invitro studies has shown that 1α 25(OH) 2 D 3 inhibits the growth of human breast cancer cells.…”
Section: Cyp24a1mentioning
confidence: 99%
“…The most commonly reported effect has been observed due to an arrest at G0/G1 to S transition of cell cycle through multiple mechanisms (Samuel & Sitrin, 2008). Several invitro studies has shown that 1α 25(OH) 2 D 3 inhibits the growth of human breast cancer cells.…”
Section: Cyp24a1mentioning
confidence: 99%
“…It is notable that activities such as regulation of synthesis of metalloproteinase and their inhibitors, activation of fibroblasts, and collagen synthesis are also considered as properties of vitamin D [9][10][11]. These evidences bring this hypothesis in mind that vitamin D can have a role in progression of hepatic damage and CLD.…”
Section: Introductionmentioning
confidence: 97%
“…9 Reseptor vitamin D merupakan anggota reseptor hormon steroid dan mengatur ekspresi gen dalam ligand-dependent manner. 7,10 Reseptor vitamin D berperan melalui jalur genomik dalam pengaturan pertumbuhan sel dan pada jalur nongenomik melalui penghambatan perkembangan dan progresivitas tumor berupa proses induksi diferensiasi seluler. Melalui ekspresi serta aktivitas enzim brushborders serta memperkuat formasi mikrovili dengan merangsang maturasi dari membran apikal mikrovili pada mukosa saluran cerna dan berperan pula dalam penghambatan proliferasi sel.…”
Section: Pendahuluanunclassified
“…Melalui ekspresi serta aktivitas enzim brushborders serta memperkuat formasi mikrovili dengan merangsang maturasi dari membran apikal mikrovili pada mukosa saluran cerna dan berperan pula dalam penghambatan proliferasi sel. 10 Penelitian menggunakan galur sel terbukti bahwa VDR berperan dalam diferensiasi sel dan menghambat proliferasi sel, hal ini menunjukkan bahwa vitamin D berperan dalam progresivitas tumor. 11 Identifikasi VDR pada jaringan tumor dengan cara pemeriksaan imunohistokimia merupakan metode yang baik dan menjadi modalitas untuk menentukan terapi target.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation